2006
DOI: 10.1021/jp065767d
|View full text |Cite
|
Sign up to set email alerts
|

Steam-Assisted Solid Wet-Gel Synthesis of High-Quality Nanorods of Boehmite and Alumina

Abstract: A simple solid-phase method was developed for synthesis of high-quality boehmite nanorods by steam-assisted wet-gel conversion process. γ-Al2O3 nanorods with clear-cut edge have been successfully obtained by thermal treatment of boehmite nanorods at 600 °C for 5 h. The nanorods of boehmite and γ-Al2O3 were characterized by X-ray diffraction (XRD), Raman spectroscopy, and field emission scanning electron microscope (FESEM) with energy-dispersive spectroscopy (EDS), transmission electron microscopy (TEM), and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
69
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 73 publications
7
69
0
Order By: Relevance
“…Two main routes are usually used to prepare boehmite with a specific morphology: (1) Al 2 (SO 4 ) 3 , AlCl 3 , Al(NO 3 ) 3 , or NaAlO 2 is often used to prepare nanofiber [7], nanowire [8][9], nanorod [10], nanoribbon [11][12], or nanosheet [13] boehmite via neutralization or hydrolysis, and (2) aluminum alkoxide is extensively used to synthesize boehmite or pseudoboehmite with the specific morphology via hydrolysis. Moreover, boehmite with 3D superstructures (e.g., stalk-like [14], cantaloupe-like [15], leaf-like [16], and flower-like [17]) has been frequently prepared through the assembly of nanofiber, nanorods, or nanosheets using the aforementioned aluminum-bearing salts or aluminum alkoxide.…”
Section: Introductionmentioning
confidence: 99%
“…Two main routes are usually used to prepare boehmite with a specific morphology: (1) Al 2 (SO 4 ) 3 , AlCl 3 , Al(NO 3 ) 3 , or NaAlO 2 is often used to prepare nanofiber [7], nanowire [8][9], nanorod [10], nanoribbon [11][12], or nanosheet [13] boehmite via neutralization or hydrolysis, and (2) aluminum alkoxide is extensively used to synthesize boehmite or pseudoboehmite with the specific morphology via hydrolysis. Moreover, boehmite with 3D superstructures (e.g., stalk-like [14], cantaloupe-like [15], leaf-like [16], and flower-like [17]) has been frequently prepared through the assembly of nanofiber, nanorods, or nanosheets using the aforementioned aluminum-bearing salts or aluminum alkoxide.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the nanofibers were synthesized in the absence of surfactant and in a supersaturated hydrothermal condition, which was reported by Shen et al [9]. This steam-assisted self-assembly fabrication of boehmite yielded high-quality 1D nanostructures with clear-cut edges and high purity.…”
Section: Scanning Electron Microscopymentioning
confidence: 80%
“…A solution-based chemical synthesis of boehmite nanofibers and alumina nanorods by a modified sol-gel process in the presence of organic solvents has been reported [8]. Shen et al reported a steam-assisted solid-phase conversion of amorphous aluminium hydroxide wet gel to well-crystallized 1D nanostructured boehmite nanorods without using surfactants and organic solvents [9]. The process is unique in the simplicity of preparation and the high efficiency of crystal growth, which can be operated on a large scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because they have a uniform pore size, high specific surface area (SSA), and thermal stability [1]. They also have tunable pores and acidities, and are therefore useful in various petrochemical processes [2]. However, their average pore size is low, which limits their use in processes that involve bulky molecules.…”
Section: Introductionmentioning
confidence: 99%